2019
DOI: 10.1155/2019/2707826
|View full text |Cite
|
Sign up to set email alerts
|

Management of Corneal Ectasia after LASIK with Phototherapeutic Keratectomy Combined with Photorefractive Keratectomy and Collagen Cross-Linking

Abstract: Background. To evaluate the efficacy of phototherapeutic keratectomy (PTK) combined with photorefractive keratectomy (PRK) and riboflavin with ultraviolet-A collagen cross-linking (CXL), performed sequentially on the same day, in the management of corneal ectasia after LASIK. Methods. This retrospective review comprised consecutive patients with corneal ectasia after LASIK. The patients were administered PTK and PRK on the previous corneal flap, and CXL was given on the same day by the same surgeon. The main o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Although many studies have demonstrated that CXL can stop the progression of the cone, improve corneal curvature and maintain BCVA over time, most patients still require refractive correction to achieve visual rehabilitation. A large number of studies have focused on combining CXL with other refractive surgeries such as PRK, LASIK, Intra‐Corneal Ring Segments (ICRS) and Phakic intraocular lenses(pIOLs), which is termed CXL plus, for the purpose of enhancing the efficacy of CXL (El‐Khoury et al, 2018; Kamburoglu & Ertan, 2008; Tamayo et al, 2017; Yildirim, Cakir, et al, 2014; Yildirim, Uslu, et al, 2014; Zhou et al, 2019).…”
Section: Treatmentmentioning
confidence: 99%
“…Although many studies have demonstrated that CXL can stop the progression of the cone, improve corneal curvature and maintain BCVA over time, most patients still require refractive correction to achieve visual rehabilitation. A large number of studies have focused on combining CXL with other refractive surgeries such as PRK, LASIK, Intra‐Corneal Ring Segments (ICRS) and Phakic intraocular lenses(pIOLs), which is termed CXL plus, for the purpose of enhancing the efficacy of CXL (El‐Khoury et al, 2018; Kamburoglu & Ertan, 2008; Tamayo et al, 2017; Yildirim, Cakir, et al, 2014; Yildirim, Uslu, et al, 2014; Zhou et al, 2019).…”
Section: Treatmentmentioning
confidence: 99%
“…It reduces irregular astigmatism and refractive error, improving visual outcomes without compromising the efficacy of CXL in keratoconus 21 and post-LASIK ectasia. 22,23 In 2019, Kaiserman et al proposed the Tel-Aviv Protocol, which recommended a combination of epithelial photorefractive keratectomy (ePRK) combined with CXL for treating keratoconus. This protocol involves removing the epithelium using a customized refractive laser profile, followed by laser ablation using the EX500 excimer laser.…”
mentioning
confidence: 99%
“…It reduces irregular astigmatism and refractive error, improving visual outcomes without compromising the efficacy of CXL in keratoconus 21 and post-LASIK ectasia. 22,23…”
mentioning
confidence: 99%